EFFICIENCY OF ORGANIZING PUBLIC SPORTS EVENTS IN EDUCATIONAL INSTITUTIONS - Xudayberdiyeva Nodira Abduyakubovna (Research Focus International Scientific Journal, 2025)
This article describes the effectiveness of public sports events in educational institutions.